Examining artificial intelligence and law as a tool for legal service, decision-making, job transformation, and ethical performance - Quezada Castro, María Del Pilar (2024)
Artificial intelligence is a tool used in law. It focuses on the complementarity of human performance. A bibliometric study of the scientific production in Scopus in the period 2015-2023 was carried out. The main findings are that artificial intelligence is related to legal service, decision-making, digital transformation, and ethical performance. It was concluded that scientific production on artificial intelligence and law experienced exponential growth, especially coinciding with the COVID-19 pandemic. It was also concluded that artificial intelligence enables the generation of empathy and creativity through responsible use, which gives rise to trust in the population.